Earnings, Schooling, and Economic Reform - Campos, Nauro; Jolliffe, Dean (World Bank, 2012)
Earnings, Schooling, and Economic Reform: Econometric Evidence From Hungary (1986 2004) Nauro Campos and Dean Jolliffe How does the relationship between earnings and schooling change with the introduction of comprehensive economic reform? This article sheds light on this question using a unique data set and procedure to reduce sample-selection bias. The principal assumptions are that sample-selection bias was minimal in 1986 and that the decision to participate in the wage market after 1986 is correlated with age, gender, and schooling demographics. Once corrected for sample selection on observables, the increase in returns is smaller, suggesting the existence of the positive correlation between education and the decision to participate in the wage sector that was discussed above. 16 Comparing the panels shows that sample-selection bias is positive and quite large throughout the period of analysis. An advantage of the Wage and Earnings Survey design is that the sample was selected in a single stage, and thus there is no need to correct estimates of the sampling variance for any design-induced dependence. Returns to Years of Schooling, 1986 2004: Spatial and Industry Fixed-effects Estimation of Equation (1) 1986 Panel A: Selection-corrected estimates Years of schooling Gender dummy variable (male 1) Potential experience Experience squared/100 Firm size dummy (300 employees 1) Number of observations R2 Panel B: Uncorrected estimates Years of schooling Gender dummy variable (male 1) Potential experience Experience squared/100 Firm size: 300 employees Number of observations R2 1989 1992 1995 1998 Although the Wage and Earnings Survey data include no direct measures of school quality, it is possible to provide limited supporting evidence. Studies that are based on multiple survey instruments for temporal analysis face the difficult question of whether the observed change results from changes in the examined population or changes in the survey instrument. The analysis showed that the 75 percent increase in returns to a year of schooling between 1986 and 2004 is evidence that the planned economy Campos and Jolliffe 525 undervalued education and that liberalization has allowed markets to correct this.